The Effect of Health Service Utilization During Childhood Illness on Stunting in Jember Regency - Alya, Alya Nabilah (Future Science, 2025)
Background: Jember Regency is a district that is included in the 100 priority districts or cities for stunting interventions with a prevalence in 2021 is 12.30%. Kalisat District is one of the 12 stunting loci sub-districts in 2021 with a prevalence of 24.98%. Based on a preliminary study at the Kalisat Health Center in 2021, it only around 291 toddlers with a coverage of 2.51% access and utilize outpatient and nutritional counseling at the Kalisat Health Center.. The low access and utilization of health services will affect the incidence of stunting in children under five. This study aims to analyze the effect of access and utilization of health services on the incidence of stunting in children under five years old in Kalisat District. Methods: This research is an observational analytic study with a case-control. The sample of this study 40 people in the case group and 40 people in the control group. Data analysis used logistic regression. Result: The results showed that utilization of health services when sick (p = 0,025; OR 2,852) affected incidence of stunting in children under five years old in Kalisat District. Conclusion: It showed that utilization of health services affected the incidence of stunting in children under five years old in Kalisat District.